Dynamic Edgeworth-Bertrand Competition - Dudey, M. (Quarterly Journal of Economics, 1992)
Journal Article Dynamic Edgeworth-Bertrand Competition Get access Marc Dudey Marc Dudey Board of Governors of the Federal Reserve System and Rice University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 107, Issue 4, November 1992, Pages 1461–1477, https://doi.org/10.2307/2118397 Published: 01 November 1992